Chapter 22 Addressing tribalism in displacement: self-directed musical activities in Blacktown’s South Sudanese community - Dieckmann, S (Brill Academic Publishers, 2020)
This chapter presents findings from an ethnographic grounded theory case study of self-directed musical activities in the South Sudanese community in Blacktown, New South Wales, Australia (Dieckmann, 2016). These activities were observed in 2011 and coincided with South Sudan attaining independence. The chapter opens with a brief overview of South Sudanese displacement, migration to Australia, and the complexity of South Sudanese tribalism. The findings examine the ways in which musical activities are used both to negotiate tribal and national identities and to mediate experiences of transnationalism in the context of resettlement. In so doing, the chapter highlights the tensions and intersections between tribalism, in which members most strongly identify with tribal kinship groups bounded by ethnicity, culture and/or language, and national affiliations, in which one’s sense of belonging is founded on allegiance to the same nation-state. The chapter concludes with reflections on the implications these musical mechanisms have for music education involving displaced persons, forced migrants, and former refugees.